A smartphone-based device for simultaneous measurement of ratiometric fluorescence and absorbance demonstrated by the determination of hypochlorous acid. (31st August 2022) - Dou, Jianzhi; Shen, Qirui; Yang, Yan; Song, Haiyan; Shen, Dazhong
Abstract : Ratiometric fluorescence and absorbance are measured simultaneously by a smartphone-based device according to the corrected brightness ratio in a picture. Abstract : Multi-signal assays can improve the accuracy of determinations by integrating the merits of each analytical signal. In the widely used fluorometric and colorimetric dual-mode, the fluorescence intensity and absorbance are measured, respectively, using a fluorophotometer and a spectrophotometer. Herein, we developed a smartphone-based portable device by sandwiching a fluorescence cuvette between two Perspex right-angle trapezoidal cubes, which can measure simultaneously the ratiometric fluorescence and absorbance. Under the irradiation of the excitation light, the fluorescence intensity of the test solution in the cuvette and the intensities of the incident and transmitted light were measured from one picture. According to the intensity ratio of the fluorescence and incident light, the ratiometric fluorescence signal was obtained. The absorbance of the test solution was estimated from the brightness ratio of two trapezoidal cubes. The applicability of the dual-mode portable device was demonstrated by the determination of hypochlorous acid using a heptamethine cyanine-based probe. The limits of detection of the ratiometric fluorescence and absorbance modes for the determinations of HClO are 0.011 and 0.13 μM, respectively, with the detectable concentration range of 0.02–10 μM in the dual-mode. The absorbance can be used to monitor the influence of the inner filter effect at the excitation wavelength on the ratiometric fluorescence intensity.